2008
DOI: 10.1128/jb.00307-08
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Mn2+and Zn2+on PsaR-Mediated Expression of the Virulence GenespcpA,prtA, andpsaBCAofStreptococcus pneumoniae

Abstract: Homeostasis of Zn2؉ and Mn 2؉ is important for the physiology and virulence of the human pathogen Streptococcus pneumoniae. Here, transcriptome analysis was used to determine the response of S. pneumoniae D39 to a high concentration of Zn 2؉ . Interestingly, virulence genes encoding the choline binding protein PcpA, the extracellular serine protease PrtA, and the Mn 2؉ uptake system PsaBC(A) were strongly upregulated in the presence of Zn 2؉ . Using random mutagenesis, a previously described Mn 2؉ -responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
110
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(118 citation statements)
references
References 90 publications
8
110
0
Order By: Relevance
“…3, the E. faecalis zntA Ef and ef0759 mutants were significantly impaired in their capacity to survive inside macrophages when compared with their parent E. faecalis VE14089. The latter was even able to divide to some extent inside macrophages for the first 2 h and only later succumbed to macrophage defences, as reported previously (Kloosterman et al, 2008). Both proteins are, indeed, relevant for survival inside macrophages.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…3, the E. faecalis zntA Ef and ef0759 mutants were significantly impaired in their capacity to survive inside macrophages when compared with their parent E. faecalis VE14089. The latter was even able to divide to some extent inside macrophages for the first 2 h and only later succumbed to macrophage defences, as reported previously (Kloosterman et al, 2008). Both proteins are, indeed, relevant for survival inside macrophages.…”
Section: Resultssupporting
confidence: 83%
“…Such a connection between zinc resistance and higher tolerance to oxidative stress and lysozyme has, to the best of our knowledge, never been described previously. A zinc burst, described to occur inside macrophages (Botella et al, 2011), could indirectly affect the mechanisms of oxidative stress response, as it is known that zinc is able to compete with manganese (Kloosterman et al, 2008;McDevitt et al, 2011), a crucial metal in oxidative stress response, in protein binding. McDevitt et al (2011) found that extracellular zinc inhibits manganese acquisition in Streptococcus pneumoniae by competing for binding to the solute-binding protein PsaA.…”
Section: Resultsmentioning
confidence: 99%
“…Since all S. pneumoniae strains tested so far have been unable to grow on fucose as a sole carbon and energy source, the role of this sugar in pneumococcal metabolism remains unclear (3). An alternative method based on the Zn 2ϩ -inducible promoter P czcD was described recently (7,17). To perform a gene depletion experiment with the Zn 2ϩ system, a DNA cassette containing a selectable antibiotic resistance marker and the gene of interest under the control of the P czcD promoter was inserted into the FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of the selected gene takes place when the Zn 2ϩ concentration in the medium is reduced. As zinc plays an important role in pneumococcal physiology, the expression and function of a number of gene products are potentially affected by the levels of this metal ion (6,16,17,21). The Zn 2ϩ depletion system should therefore be used with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc homeostasis is achieved by the tight control of storage systems and transporters with broad diversity (5,15,30,50). Bacterial responses to zinc have been studied by genome-wide transcriptional analyses in Escherichia coli (8,26), Bacillus subtilis (31), and Streptococcus pneumoniae (24), showing altered expression of numerous genes implicated in tolerance for and efflux of zinc and other metals, and also in general stress resistance. Conversely, zinc depletion in E. coli regulates a small number of genes involved in high-affinity zinc binding and uptake or encoding zinc-independent ribosomal proteins (18).…”
mentioning
confidence: 99%